A dmp‐type Microporous Cadmium(II)‐Isonicotinate: Synthesis, Structure and CO2 Adsorption Property. Issue 8 (13th March 2014) - Zhang, Zhihua
Abstract The 4‐connected dmp‐type cadmium(II)‐isonicotinate framework [Cd(isonic)2(H2O)]n·n(DMA) (1) (isonic = isonicotinate, DMA = N, N′‐dimethylacetamide) was obtained by the solvothermal reactions of Cd(NO3)2 and isonicotinic acid (Hisonic). Compound 1 features a 3D porous framework with the opened channels occupied by the lattice DMA molecules. Thermal analysis reveals that such framework remains much stable after removal the free DMA molecules. CO2 adsorption measurement shows that such framework exhibits notable CO2 adsorption behavior.